Construção fragmentada: uma análise gerencial dos processos construtivos do complexo de prédios do Instituto de Educação Matemática e Científica (IEMCI) da UFPA - BORDALO, Rosa Helena Coutinho (Universidade Federal do Pará, 2013)
In recent years the Federal University of Pará (UFPA), among other important precautions, has invested significantly in the restructuring and expansion of its campi, the construction of new buildings, expansion and renovation of the existing ones. As in most IFES, however, the UFPA has no structure or enough time for the responsible technical crew to manage and develop constructive project execution, monitor and supervise the construction works and maintenance. The objective of this study is to make a management analyze of the construction processes at the UFPA, on the basis of the complex of buildings of the Institute of Mathematics and Science Education (IEMCI), aiming the identification and minimization of the problems presented along its flow. To do so, through a case study of the administrative procedures and other documents related to the construction of the various modules that make up the Institute, with the data collection of all the performed works, and conducting interviews, based on the Campos's model (2011), to everyone involved in the process. After analyzing the results, the conclusion was that a lack of planning and effective management of constructive processes produced several problems, among them, incomplete and flawed projects, leading to fragmented construction. The construction executed through stages cost 35.19% more than if it was performed in one step and in its entirety. And as the term, this increase was even greater, reaching 283%. Concluding that the interveners caused by fragmentation, seriously influenced on the deadline and the final cost of the construction.